Advanced Remote Data Acquisition Using a Pop-Up Data Shuttle (PDS) to Report Data From Current- and Pressure-Recording Inverted Echo Sounders (CPIES) - Jeon, Chanhyung; Park, Jae-Hun; Kennelly, Maureen; Sousa, Erran; Watts, D. Randolph; Lee, Eun-Joo; Park, Taewook; Peacock, Thomas (Frontiers in Marine Science, 2021)
A current- and pressure-recording inverted echo sounder (CPIES) placed on the sea floor monitors aspects of the physical ocean environment for periods of months to years. Until recently, acoustic telemetry of daily-processed data was the existing method for data acquisition from CPIES without full instrument recovery. However, this approach, which requires positioning a ship at the mooring site and operator time, is expensive and time-consuming. Here, we introduce a new method of obtaining data remotely from CPIES using a popup-data-shuttle (PDS), which enables straightforward data acquisition without a ship. The PDS data subsampled from CPIES has 30–60 min temporal resolution. The PDS has a scheduled pop-up-type release system, so each data pod floats to the sea surface at a user-specified date and relays the recorded data via the Iridium satellite system. We demonstrated the capability of an array of PDS-CPIES via two successful field experiments in the Arctic Ocean. The data acquired through the PDS were in agreement with the fully recovered datasets. An example of the data retrieved from the PDS shows that time-varying signals of tides and high-frequency internal waves were well captured. GPS-tracked trajectories of the PDS floating free at the sea surface can provide insights into ice drift or ocean surface currents. This PDS technology provides an alternative method for remote deep-ocean mooring data acquisition.